2021
DOI: 10.1093/jtm/taab088
|View full text |Cite
|
Sign up to set email alerts
|

Determining quarantine length and testing frequency for international border opening during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has resulted in the closure or partial closure of international borders in almost all countries. Here we investigate the efficacy of imported case detection considering quarantine length and different testing measures for travellers on arrival. Methods We examine 8 broad border control strategies from utilising quarantine alone, pretesting, entry and exit testing, and testing during quarantine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…23 Our estimate of 60-65% is also consistent with the results from a previous modelling study. 24 In the worst-case scenario wherein infected travellers are infected right before arrival, testing upon arrival without quarantine would have no effect on their FOI because their viral load upon arrival would be below the detection threshold. Fully vaccinated inbound travellers would have their expected FOI lowered by σ m due to the vaccine reducing their susceptibility to infection.…”
Section: Resultsmentioning
confidence: 99%
“…23 Our estimate of 60-65% is also consistent with the results from a previous modelling study. 24 In the worst-case scenario wherein infected travellers are infected right before arrival, testing upon arrival without quarantine would have no effect on their FOI because their viral load upon arrival would be below the detection threshold. Fully vaccinated inbound travellers would have their expected FOI lowered by σ m due to the vaccine reducing their susceptibility to infection.…”
Section: Resultsmentioning
confidence: 99%
“…Two modelling studies on microbiological detection (10, 14) were identified in the updated search. Assuming that exposure had occurred, pre-departure testing was predicted to improve the detection of cases by up to 84.4%, although results vary according to timing of the test.…”
Section: Resultsmentioning
confidence: 99%
“…Two modelling studies (9, 10) demonstrated that a combination of quarantine and microbiological detection with a PCR test at day 7 significantly increases the proportion of cases averted as compared with quarantine alone, thus reducing the quarantine period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, mandatory testing before the travel and on arrival has been recommended by many governments; and the length of the quarantine can be determined according to the results of the tests. Moreover, the risk level of the destination and the travelers' origin can be influential (8). In spite of this evidence about the flexibility in the period of quarantine, some other federal or local governments insist on applying 14-day quarantine for international travelers.…”
mentioning
confidence: 99%